2008
DOI: 10.1128/jvi.00018-08
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Human Immunodeficiency Virus Type 1 CRF01_AE Protease in Complex with the Substrate p1-p6

Abstract: The effect of amino acid variability between human immunodeficiency virus type 1 (HIV-1) clades on structure and the emergence of resistance mutations in HIV-1 protease has become an area of significant interest in recent years. We determined the first crystal structure of the HIV-1 CRF01_AE protease in complex with the p1-p6 substrate to a resolution of 2.8 Å. Hydrogen bonding between the flap hinge and the protease core regions shows significant structural rearrangements in CRF01_AE protease compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Additionally, the possibility for dipolar broadening as a result of doubly-labeled protease has been eliminated by pulsed EPR distance measurements that indicated the distances between the labels exceed 25 Å and generally range from 28 -42 Å depending on protease flap position [17]. These values are in general agreement with molecular dynamic simulations [28] and predictions from known crystal structures [29][30][31]. From these findings, buffers for all EPR experiments are prepared at low ionic strength, typically 2 mM NaOAc with no additional salts.…”
Section: Affect Of Ionic Strength On Protein Aggregationsupporting
confidence: 56%
“…Additionally, the possibility for dipolar broadening as a result of doubly-labeled protease has been eliminated by pulsed EPR distance measurements that indicated the distances between the labels exceed 25 Å and generally range from 28 -42 Å depending on protease flap position [17]. These values are in general agreement with molecular dynamic simulations [28] and predictions from known crystal structures [29][30][31]. From these findings, buffers for all EPR experiments are prepared at low ionic strength, typically 2 mM NaOAc with no additional salts.…”
Section: Affect Of Ionic Strength On Protein Aggregationsupporting
confidence: 56%
“…This effect is even more pronounced in subtype AE, where N88S pulls D30 out of the active site (21). We also showed that D30 not only is key for inhibitor binding but also is essential for recognition of the p1-p6 cleavage site (8,15,22). Consequently, the D30N mutation, which lowers affinity for NFV (23), also likely compromises p1-p6 recognition, leading to coevolution of this cleavage site (15).…”
Section: H Uman Immunodeficiency Virus Type 1 (Hiv-1) Protease (Pr)mentioning
confidence: 79%
“…Nevertheless, the impact of mutations outside of the active site also impacts evolution of drug resistance. These include changes in the core of HIV-1 protease either due to natural differences in the HIV clades [47] or compensatory mutations to maintain fitness or can involve changes in substrate sequence. Changes in the beta-barrel core of the protease monomers have been associated with compensatory mutations, such the existence of N88D allowing the simultaneous occurrence of D30N and L90M [48].…”
Section: Additional Challenges To Inhibitor Design From Sequence Evolmentioning
confidence: 99%